Measurement and correlation of electrical conductivity of ionic liquid [EMIM][DCA] in propylene carbonate and γ-butyrolactone. (20th August 2015) - Xu, Li; Cui, Xianbao; Zhang, Ying; Feng, Tianyang; Lin, Ruirong; Li, Xiaobing; Jie, Huimin
Abstract: Electrical conductivities of ionic liquid (IL) 1-ethyl-3-methylimidazolium dicyanamide ([EMIM][DCA]) in propylene carbonate (PC) and γ-butyrolactone (GBL) were measured and correlated. The effects of temperature and IL concentration on the electrical conductivity were investigated comprehensively. The electrical conductivity of mixture increases with increasing temperature. When the mole fraction of IL in mixture increases from 0 to 1, electrical conductivity increases to a maximum value, and then decreases with IL mole fraction. Besides, the maximum point moves to high IL concentration as temperature increasing. The electrical conductivity data were correlated by Vogel-Tamman-Fulcher (VTF) and Arrhenius equation. VTF equation describes the temperature dependence of electrical conductivity with high precision, but it cannot be used to describe the effects of IL concentration. Arrhenius equation is able to describe the temperature and IL concentration dependence of electrical conductivity, but the accuracy is modest. In Arrhenius equation, the relationship between parameters (activation energy Ea and pre-exponential factor A ) and the mole fraction of IL were obtained. Taking advantages of both Arrhenius equation and VTF equation, we proposed an improved four-parameter equation (quasi-Arrhenius equation) to correlate the electrical conductivity, in which the dependence of temperature and IL concentration were included, and the correlation results agreed well with experimental data.